Bibliometric Analysis of the Term “Entrepreneurial Motivation” - Mudassir, Andi; Yuswono, Irawan; Usmany, Paul; AJi, Lexi Jalu (International Journal of Business, Law, and Education, 2024)
This study presents a comprehensive bibliometric analysis of the term "Entrepreneurial Motivation," reflecting the extensive scholarly interest in the determinants that incite individuals to undertake entrepreneurial endeavors. Utilizing a dataset from reputable databases such as Scopus, this research elucidates the evolution of entrepreneurial motivation as a concept and its significance in the entrepreneurship literature. We investigate key thematic clusters, seminal works, influential authors, and collaboration patterns in the field. Additionally, we explore publication trends in leading journals and identify research lacunae and emerging trends that signal future scholarly directions. Our findings indicate a robust engagement with factors such as educational background, personal traits, and socio-economic impacts, including the influence of the COVID-19 pandemic on entrepreneurial activity. The study also highlights potential new avenues for research in areas that have yet to become prominent within the existing literature, such as the role of risk perception, necessity entrepreneurship, passion, and social responsibility in shaping entrepreneurial motivation. This analysis provides a detailed landscape of the field, contributing to a more nuanced understanding of the dynamic forces that foster and sustain entrepreneurial motivation in an ever-evolving global economy.